Espiritualidad en un Grupo de personas con enfermedad terminal Radicados en Bogotá, Colombia, en la Localidad de Engativá (2021)
This degree work focuses on the way in which a group of terminal patients live spirituality, basically from a religious and emotional perspective, based on the difficulty of assuming detachment from people who are loved, from their personal goals, which are truncated, and in the same way, of everything that as people can get to bind the world.